The effect of acidulated phosphate fluoride (APF) gel against erosion on enamel microstructure of primary teeth which soaked with Citrus aurantifolia - Lai Yi, Flora Ng; Riyanti, Eriska; Gartika, Meirina (Universitas Padjadjaran, 2022)
ABSTRACTIntroduction: Erosion is a common dental problem that is especially prevalent in children due to the increasing consumption of acidic food and beverages. APF gel is believed to be effective in reducing the demineralization effect of the teeth as well as escalating the remineralization process. This research aims to determine and evaluate the effectiveness of 1.23% APF gel as a preventive agent for the erosion of tooth enamel, specifically in deciduous teeth. Methods: This type of research is true experimental research. The population of this research would be primary teeth extracted from children, using a purposive sampling technique with inclusive and exclusive criteria. A total amount of 5 maxillary primary central incisors were extracted and cleaned. APF gel was applied repetitively on the left side of the teeth for 4 minutes every hour, whereas the right side was left as it is. Samples were then analyzed using a scanning electron microscope (SEM). A qualitative and subjective analysis regarding the micromorphological features of the erosion can be done. Result: The side of teeth without APF gel application has a greater erosion rate compared with teeth with APF gel application. The tooth which is demineralized shows a honeycomb structure of the interprismatic enamel. As for the dentinal tubules, teeth without APF gel application have a bigger opening of dentinal tubules, going up to 7.868 micrometers in size compared to teeth with APF gel application (1-2 micrometers). Conclusion: The application of professional acidulated phosphate fluoride (APF) gel on deciduous teeth even when soaked in Citrus aurantifolia, is proven to be effective in preventing dental erosion.Keywords: acidulated phosphate fluoride (APF) gel; citrus aurantifolia; dental erosion; primary tooth